Local History Learning in the Society 5.0 Era: A Study at Universities in Jakarta, West Java, and Banten: Pembelajaran Sejarah Lokal pada Era Society 5.0: Studi pada Perguruan Tinggi di Jakarta, Jawa Barat, dan Banten - Nur Fajar Absor; Lobelia Asmaul Husna; Djunaidi Djunaidi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study explores the implementation of local history learning in higher education within the framework of the Society 5.0 era, which seeks to balance technological progress with human-centered values. The research is grounded in the growing need to integrate digital technologies, such as the Internet of Things (IoT) and Artificial Intelligence (AI) into history education, which has traditionally relied on conventional approaches. Using a qualitative descriptive method, the study was conducted in three regions: Jakarta, West Java, and Banten. Data was collected through interviews and document analysis involving three lecturers who teach Local History courses and analyzed using the Miles and Huberman model. The results indicate that local history is understood as the study of local events and values that strengthen regional and national identity. In the context of Society 5.0, local history learning has begun to utilize digital tools, including online archives, educational videos, and AI-based applications; however, implementation remains uneven among universities. Learning methods vary from project-based learning and field trips to discovery-based approaches. The study identifies major challenges, including limited access to online historical resources, low academic writing proficiency among students, and ethical concerns related to AI use. Conversely, digital integration presents opportunities to expand access to historical materials and enhance students’ engagement with local history. The study concludes by emphasizing the need for curriculum development involving professional organizations, particularly the Indonesian Association of History Education Study Programs (P3SI), to align local history education with the Society 5.0 paradigm.